Effect of nalfurafine hydrochloride on the basal pressure of the sphincter of Oddi in anesthetized rabbits - Kobayashi, Ryosuke; Nakao, Kaoru; Yamada, Kiyoshi; Miyamoto, Yohei; Mochizuki, Hidenori (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Opioid analgesics, which are classified as μ-opioid receptor agonists, are known to induce spasms or contraction of the sphincter of Oddi (SO), thereby inducing or exacerbating biliary diseases such as biliary obstruction, gallbladder dysfunction, cholelithiasis, pancreatitis, biliary dyskinesia, cholangitis, and cholecystitis. However, effects of κ-opioid receptor agonists on SO contraction have not been clarified. In the present study, we investigated the effect of nalfurafine hydrochloride (nalfurafine), (E)-N-[17-(cyclopropylmethyl)-4,5α-epoxy-3,14-dihydroxymorphinan-6β-yl]-3-(furan-3-yl)-N-methylprop-2-enamide monohydrochloride, a selective κ-opioid receptor agonist, on spontaneous contraction of rabbit SO. Methods: SO contraction was measured using manometry in anesthetized rabbits. Rabbits were anesthetized with intravenous administration of 25 mg/kg sodium pentobarbital. An open tip catheter was inserted into the common bile duct toward the SO ampullae. Saline was perfused through the lumen of the open tip catheter at a constant rate of 6 ml/hr using a syringe pump. Nalfurafine, morphine, and pentazocine were intravenously (i.v.) administered and perfusion pressure was recorded. Results: Morphine (0.3 mg/kg, i.v.) and pentazocine (3 mg/kg, i.v.) were found to increase SO perfusion pressure, suggesting that these opioid analgesics may cause SO contraction. In contrast, nalfurafine (0.2 μg/kg, i.v.) decreased the perfusion pressure, indicating that this κ-opioid receptor agonist suppresses SO contraction. Conclusions: These findings suggest that nalfurafine is unlikely to induce or exacerbate biliary diseases and may be safely used in patients with these disorders.